Optimization of Archive Digitization at the Padjadjaran University Central Library - Alamsyah, Novana Noer; Kusnandar, Kusnandar; Sukaesih, Sukaesih (Ilmu Informasi Perpustakaan dan Kearsipan, 2023)
Digitizing archives or converting archival media from conventional to digital is one way to optimize archive management in an institution so that archives can be archived more efficiently and easily accessed. The purpose of this study is to provide an overview of the optimization of the digitization of archives in the Central Library of Padjadjaran University. The method  used  is  descriptive qualitative. Techniques in  data  collection, researchers carried out three series of stages, namely interviews, observation and literature study. The results of this study show that the digital archives at the Padjadjaran University Central Library are compiled in a system called e-Office and centralized with the Padjadjaran University Record Center. With this digital archive, archivists and users can easily access it simultaneously and make it easier to retrieve information. Digital archive management goes well through four stages, namely creation, use, maintenance, and depreciation. However, there are still obstacles that are experienced, including the low awareness of some higher education institutions in collecting files for digital archives, a lack of human resources with special expertise in the field of archiving, and a lack of human resources with expertise in technology. It can be concluded, the digitization of archives and their overall management at the Padjadjaran University Central Library is considered optimal.